2007
DOI: 10.1080/00224490701263595
|View full text |Cite
|
Sign up to set email alerts
|

First Stirrings: Cultural Notes on Orgasm, Ejaculation, and Wet Dreams

Abstract: Both the findings and the limitations of numeric milestone research in sexology have a bearing on the pedagogical status of pleasure, as well as the cultural underpinnings of the notion of a psychosexual milestone. An overview is offered of international data pertaining to the chronology of three "milestones" in sexual autobiography: first orgasm (orgasmarche), first ejaculation (oigarche), and first wet dream (nocturnal emission). Methodological problems associated with the measurement of these variables are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…This pubertal criterion can be considered as the counterpart of the menarche in girls (Carlier & Steeno, 1985). Different names are used for the first ejaculation – oigarche (Carlier & Steeno, 1985; Janssen, 2007), spermarche (Hirsch et al. , 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pubertal criterion can be considered as the counterpart of the menarche in girls (Carlier & Steeno, 1985). Different names are used for the first ejaculation – oigarche (Carlier & Steeno, 1985; Janssen, 2007), spermarche (Hirsch et al. , 1985).…”
Section: Introductionmentioning
confidence: 99%
“…, 1985). In this study, we are using ejacularche as a synonym for the first conscious ejaculation or even more appropriate age of remembered first ejaculation (Janssen, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their semen, if any, is not yet capable of fertilization [Janczewski & Bablok 1985]. This is also the typical age at which the testes start to enlarge and pubic hair appears [Tanner 1962], and at which boys experience their first ejaculation and orgasm [Janssen 2007]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies on China, Denmark, France, Hungarian, and Copenhagen present growth chart of body size, age at spermarche, and urinary excretion of spermatozoa. However, none of these studies showed the relationship between age at spermarche and body size (Schaefer et al 1990;Pedersen et al 1993;Yan et al 1999;Rochebrochard 2000;Ji 2001;Bodzsar & Zsakai 2007;Janssen 2007;Zhu et al 2009). On the other hand in Sragen (center of Java) peak height velocity of the boys is reported to reach at the same time as their age at spermarche; however, their peak weight velocity reached before that (Suratno 2009).…”
Section: Introductionmentioning
confidence: 94%